Isolation of Human Innate Lymphoid Cells. (29th June 2018) - Krabbendam, Lisette; Nagasawa, Maho; Spits, Hergen; Bal, Suzanne M.
Abstract: Innate lymphoid cells (ILCs) are innate immune cells of lymphoid origin that have important effector and regulatory functions in the first line of defense against pathogens, but also regulate tissue homeostasis, remodeling, and repair. Their function mirrors T helper cells and cytotoxic CD8 + T lymphocytes, but they lack expression of rearranged antigen‐specific receptors. Distinct ILC subsets are classified in group 1 ILCs (ILC1s), group 2 ILCs (ILC2s), and group 3 ILCs (ILC3s and lymphoid tissue–inducer cells), based on the expression of transcription factors and the cytokines they produce. As the frequency of ILCs is low, their isolation requires extensive depletion of other cell types. The lack of unique cell surface antigens further complicates the identification of these cells. Here, methods for ILC isolation and characterization from human peripheral blood and different tissues are described. © 2018 by John Wiley & Sons, Inc.